An assessment of format radio in the Philippines as applied to 99.5RT, CitiLite 88.3 and NU107 - Pedero, Joselito N. (2008)
"This study sought to find out how effective was the use of the concept of format radio on three Philippine FM stations that adopted it in Metro Manila. Music stations 99.5RT, Citilite 88.3 and NU107 were choses for this study primarily because they used and followed the concept and strictly adhered to the elements. The use of format radio in these stations were also important as it showed how the concept is applied to any type of radio format. The focus of this study is on the development of format radio in the Philippines; identification of its elements; their used in the three stations studied; factors or variables that helped in their use; and its effects on the performance of the stations. Using the system's theory of management, the researcher mainly used participant observation as method for constructing data. Primary sources of data are his hands-on and long experiences in programming the three radio stations. Secondary sources are interviews with former and present members of the program staff of the stations. With 99.5RT and Citilite 88.3 having reformatted and all of their former staffers who experienced format radio already gone, respondents for these stations were mainly former employees of the two stations, while at NU107, both former and present program staff members were interviewed. The station is still using format radio presently to great success. Analysis of documents pertinent to the study was also undertaken. Results of this study shows that format radio, also known as modern radio programming, is workable as a programming scheme for any type of format and market. The main element, especially for the on-air sound, is total control of all that is broadcasted. However, being able to adapt to changes in the market is also survey, as well as constant inter-action with the audience. Simple call-ins, song requests, texts (SMS), e-mails and personal contacts thru the stations' promotional activities which are normally done in public, are some of the ways to "feel" the audience. Image enhances the brand of the station, which can be had through the use of creative and exciting promotions, station activities as well as being in touch and giving back something to the community. Full support and direct participation by management should also be considered, and timing can be an advantage in the station's format implementation. Format radio may not be the solution to the prevailing woes of music stations in the country, especially in a major market like Metro Manila, but it can be the start of knowing more about the science of radio programming. Further researches and studies on other similar programming approaches are recommended."
Thesis (M.A. Broadcast Communication)--University of the Philippines, Diliman.
"April 2008."
Keywords: Format radio broadcasting -- Philippines -- Manila Metropolitan Area; Popular music radio stations -- Philippines -- Manila Metropolitan Area; Music radio stations -- Philippines -- Manila Metropolitan Area; Radio broadcasting -- Philippines -- Manila Metropolitan Area